RANCANG BANGUN APLIKASI SELULER PENYEDIA JASA PERAWATAN DAN KECANTIKAN MENGGUNAKAN FRAMEWORK FLUTTER - Maylia Suhendro, Jauzaa; Sudarma, Made; Care Khrisne, Duman (Jurnal SPEKTRUM; Vol 8 No 2 (2021): Jurnal SPEKTRUM, 2021)
The development of technology in this era of globalization has provided many benefits in human life, one of which is smartphones. In this modern era, looking neat and attractive is a daily necessity for people, especially women. To get beauty care services, people usually have to look salons and wait their turn. This takes a long time for beauty care service enthusiasts. Based on the existing background, a beauty care service provider application design was built using the flutter framework and android operating system with the aim of making it easier for users to find care and beauty services. In this application there are 3 users, namely Administrators who are in charge of controlling Customer and Partner data, Customers as users who are looking for care and beauty services, and Partners as people who offer care and beauty services. Based on tests carried out using the Black Box method, the overall functionality of the application has been declared successful in accordance with its respective functions and objectives. While the test results using the System Usability Scale (SUS) method in the application, respondents gave a score with an average value of 73.75 which means that the test results have a value above average. It can be concluded that the application can run well and can be Accepted (Acceptable).